Assessing the Analgesic Efficacy of Lumbosacral Epidural Morphine in Cats Undergoing Ovariohysterectomy: A Comparative Study of Two Doses - Martins, Ludimilla C. T.; Guimarães, Jéssica B.; Ferraz, Henrique T.; de Oliveira, Flávia Augusta; Gomes, Leidiane de S.; Chafes, Clóvis Júnior C.; Santos, Thalita de C. C.; Ogliari, Kaline; de Moraes, Reiner S. [UNESP]; Ribeiro, Diego [UNESP]; Ramos, Dirceu Guilherme de Souza; Rocha, Thiago André S. de S.; et al. (MDPI, 2024)
Opioids are administered epidurally (PV) to provide trans- and postoperative analgesia. Twenty healthy female cats aged between 6 and 24 months and weighing between 2 and 3.7 kg, undergoing elective ovariohysterectomy (OVH), were induced with propofol (8 mg/kg), followed by continuous infusion (0.1–0.4 mg/kg/min). Three groups were defined: CG (0.1 mL/kg of iodinated contrast, n = 6), G0.1 (0.1 mg/kg of morphine, n = 7), and G0.2 (0.2 mg/kg of morphine, n = 7) per VP. All received 0.1 mL/kg of iodinated contrast per VP and injection water to obtain a total of 0.3 mL/kg. Heart rate (HR), systolic blood pressure (SBP), temperature, expired CO2, oxygen saturation, and number of rescue analgesics were monitored. Postoperatively, a multidimensional scale was used to assess acute pain in cats for 12 h. The mean HR and SBP in the CG were higher at the time of maximum noxious stimulation and required fentanyl in all groups. Postoperatively, 83%, 28%, and 7% of the animals in CG, G0.1, and G0.2, respectively, received rescue analgesia. In cats undergoing OVH, epidural morphine at doses of 0.1 and 0.2 mg/kg did not prevent the need for intraoperative rescue analgesia but reduced the postoperative analgesic needed.
Keywords: analgesia; cats; pain; propofol; rescue